Validation of the scale Appreciation of Self Care Agency (ASA) for Costa Rica, for people with chronic disease - Leiva Díaz, Viriam (2016)
Introduction. This paper presents the results of the validation process of appearance, content and internal consistency of the second Spanish version of the ASA scale with Costa Rican adult population with chronic disease. Self-care theory developed by Dorothea Orem (1983) coined the term self-care agency, defined as "the ability to engage in self-care" (p.112), which has been the foundation of international instruments as scale Exercise Self Care Agency.Method. It was a descriptive study with a quantitative and psychometric approach, conducted with a sample of 106 people.Result. The test Kaiser-Meyer-Olkin (KMO) gave acceptable data rate of 0.65; the Bartlett test of sphericity was statistically significant with a p-value <0.000; Gl 276 and 563.9 chi. Likewise, the study by the ACP factorial method with Varimax rotation analysis suggested 5 factorial axes which accounted for 56.76% of the total variance. Cronbach's alpha was 0.84 (84%), which means that the total of the items that fail to measure the scale includes the same concept, or positively correlated.Conclusion. It managed to say that the instrument has adequate content validity, with valid and appropriate psychometric properties also demonstrated high reliability